Pendekatan Konsep Arsitektur Perilaku Pada Bangunan Pusat Rehabilatasi Orang Dengan Gangguan Jiwa (ODGJ) Di Kota Depok - Pradnya Anindya Paramitha; Lia Rosmala Schiffer (Fakultas Teknik - Universitas Bung Karno, 2025)
Kota Depok is part of the Jabodetabek metropolitan area and is located in the southern part of the Special Capital Region of Jakarta. In 2023, the population of Kota Depok was recorded at 2,123,349, with 71% in the productive age group. The Health Office of Kota Depok revealed that throughout 2022, there were 1,877 individuals with severe mental disorders, among whom many were in the productive age range of 15 to 59 years. Given the high number of patients with mental disorders in Kota Depok, the lack of a mental rehabilitation center has become a serious issue. The planning of a rehabilitation center for mental health patients in Kota Depok is expected to help address this problem by adopting the theme of Behavioral Architecture design, which will adapt to the habits and behaviors of users as a form of supportive therapy to help patients return to normalcy.